Bennett motion analysis based on specific regulus. Issue 2 (1st January 2013) - Qu, Haibo; Fang, Yuefa; Guo, Sheng
In this paper, the kinematic characteristics of Bennett mechanism and its corresponding regulus are analysed. The screw theory is employed for the analysis of twists and wrenches acted on the specific hyperboloid, and the common constraints are obtained. Through the DOF analysis, we find that the DOF of 4-R mechanism with its joint axes lying on a given regulus is equal to constant one. The general basic Bennett twists are obtained after the analysis of special cases, and the Bennett twists are determined by the given regulus. When the characteristic of Bennett mechanism degenerated, the typical single loop Bennett type mechanisms are obtained.